A Peer Review Support System Aimed at Learning Writing in High School - Bigolin, Marcio (2023)
Abstract: To assist the writing process, a tool was developed using peer review, whose creation and implementation started from an initial survey of the criteria to be used in the review of texts. High school students were chosen as the target audience. The criteria required for the writing of the National High School Exam (ENEM) were used, classified according to the cognitive model of Reading for Evaluation. In the modeling and survey of these requirements, direct interviews were conducted with potential users, as well as validation with Portuguese teachers. After using the tool, a focus group was held with some of the students. The analysis of the data and the comparison of the initial and final essays allowed us to verify that the peer review process enabled the improvement of the students’ writing process.Keywords: Review; Peer review; Writing; ENEM; Revisão Online.